1987
DOI: 10.1111/j.1600-0870.1987.tb00317.x
|View full text |Cite
|
Sign up to set email alerts
|

Heating by organized convection as a source of polar low intensification

Abstract: The paper discusses some observeti characteristics which have not been taken into account in previous theoretical studies. For instance, a well-mixed convective boundary layer is a common feature of the synoptic situation when polar lows are observed. However, in the polar lows themselves, the convection seems to reach much higher levels. Also, many polar lows have a characteristic central domain with especially strong winds and large vorticity.A simple linear CISK model is used to estimate the intensification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It varies from a few percent in the northeast (over sea ice) to 10%-15% (up to 30% in some years) in the southwest (over open water). It has also been suggested that the convective self-organization of cumuli clouds into cloud cells and rolls (cloud streets) might intensify polar storms (Okland 1987).…”
Section: Cloudiness In the Nbk Region Of The Arctic: A Reviewmentioning
confidence: 99%
“…It varies from a few percent in the northeast (over sea ice) to 10%-15% (up to 30% in some years) in the southwest (over open water). It has also been suggested that the convective self-organization of cumuli clouds into cloud cells and rolls (cloud streets) might intensify polar storms (Okland 1987).…”
Section: Cloudiness In the Nbk Region Of The Arctic: A Reviewmentioning
confidence: 99%
“…The strong baroclinicity in some cases can be partially attributed to sharp horizontal contrasts between snow-and ice-covered regions and areas of relatively warm open ocean. The flow of cold air from ice-and snow-covered regions to relatively warm ice-free ocean surfaces also triggers strong surface heat fluxes, convection, and latent heating, which can have a profound impact on polar low characteristics [Økland, 1987;Bresch et al, 1997;Yanase et al, 2004].It has become clear that these different influences result in a "spectrum" of dynamical mechanisms broadly ranging from mainly baroclinic dynamics through to polar lows driven mainly by convection [Rasmussen and Turner, 2003]. Yanase and Niino [2007] showed, using an idealized model setup, that the transition between baroclinic systems (often associated with comma clouds) and barotropic systems (with more axisymmetric vortices), is quite smooth.…”
mentioning
confidence: 99%
“…The strong baroclinicity in some cases can be partially attributed to sharp horizontal contrasts between snow-and ice-covered regions and areas of relatively warm open ocean. The flow of cold air from ice-and snow-covered regions to relatively warm ice-free ocean surfaces also triggers strong surface heat fluxes, convection, and latent heating, which can have a profound impact on polar low characteristics [Økland, 1987;Bresch et al, 1997;Yanase et al, 2004].…”
mentioning
confidence: 99%
“…primary mechanism in mesoscale cyclogenesis [Mansfield, 1974;Okland, 1987;Moore and Peltier, 1989;Wiin-Nielsen, 1989;Emanuel and Rotunno, 1989;Graig and Cho, 1989;Fantini and Buzzi, 1992]. Cyclogenesis is further enhanced by other mechanisms, such as air-sea interaction [Emanuel and Rotunno, 1989] or diabatic heating which reduces the static stability [Graig and Cho, 1989].…”
mentioning
confidence: 99%